2006
DOI: 10.1017/cbo9780511607226
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Processes and Financial Markets

Abstract: The authors examine the conditions under which democratic events, including elections, cabinet formations, and government dissolutions, affect asset markets. Where these events have less predictable outcomes, market returns are depressed and volatility increases. In contrast, where market actors can forecast the result, returns do not exhibit any unusual behavior. Further, political expectations condition how markets respond to the political process. When news causes market actors to update their political bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 0 publications
4
129
0
4
Order By: Relevance
“…41 This is consistent with recent results in international political economy such as Bernhard and Leblang (2006). Second, presidential approval is expected to have a contemporaneous effect on interest rates and on the reaction of the Federal Reserve (Beck 1987, Williams 1990, Morris 2000.…”
Section: The Macro-political Economy In Terms Of a Bayesian-svar Modelsupporting
confidence: 75%
“…41 This is consistent with recent results in international political economy such as Bernhard and Leblang (2006). Second, presidential approval is expected to have a contemporaneous effect on interest rates and on the reaction of the Federal Reserve (Beck 1987, Williams 1990, Morris 2000.…”
Section: The Macro-political Economy In Terms Of a Bayesian-svar Modelsupporting
confidence: 75%
“…Elections are among the main types of political events to elicit market reactions. As democratic turnover has the potential to affect returns to capital through shifts in the orientation of economic and regulatory policy, investors pay close attention to elections, trying to assess the probabilities of future policies and to form expectations of future returns (Sattler, 2013;Bechtel, 2009;Bernhard and Leblang, 2006). Political events in the United States, in particular, have the potential to affect investor behavior on a global scale.…”
Section: The 2016 Election and International Financial Marketsmentioning
confidence: 99%
“…While it has been extensively shown that national elections affect outcomes in financial markets, existing work has largely focused on their impact on domestic markets (e.g. Bechtel, 2009;Sattler, 2013;Bernhard and Leblang, 2006;Leblang and Mukherjee, 2005; though see Bernhard and Leblang, 2006, Ch. 4).…”
Section: Introductionmentioning
confidence: 99%
“…Why did market sentiments change rather abruptly in late 2009 and early 2010? Some scholars working on the political economy of currency crises and debt crises argue that that in order to understand the divergence between a country's economic fundamentals and the pricing of its currency or sovereign debt, it is necessary to take into account political as well as economic factors during crises periods (Bernhard and Leblang 2006;Leblang and Satyanath 2006). Building on and contributing to this literature, Chang and Leblond (2015) argue that macroeconomic indicators, such as the levels of debt and deficit provide only a partial explanation for differences in bond yields.…”
Section: The International Political Economy Of the Sovereign Debt Crmentioning
confidence: 99%